Digital Marketing and Marketing Performance: The Mediating Role of Big Data Analytics in Indonesian Logistics Firms - Hikmah Sekarningtyas; Lenni Lukitasari (Manunggal Halim Jaya, 2026)
This study investigates the effect of digital marketing on marketing performance and examines the mediating role of big data analytics in Indonesian logistics firms. The study is grounded in the Resource-Based View (RBV) and Technology Organization Environment (TOE) frameworks, which emphasize the strategic importance of digital capabilities in enhancing organizational competitiveness. A quantitative explanatory approach with a cross-sectional design was employed. Data were collected from 350 respondents working in logistics companies in Indonesia using purposive sampling combined with company-size stratification. The questionnaire instruments were developed based on previous studies and validated through expert review and pilot testing. Reliability and validity assessments indicated satisfactory results, with Cronbach’s alpha and Composite Reliability values exceeding 0.70 and Average Variance Extracted (AVE) values above 0.50 for all constructs. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings revealed that digital marketing positively and significantly affects marketing performance (β = 0.32, p < 0.001) and big data analytics (β = 0.76, p < 0.001). Furthermore, big data analytics significantly influences marketing performance (β = 0.41, p < 0.001) and partially mediates the relationship between digital marketing and marketing performance (β = 0.31, p < 0.001). The model demonstrated substantial explanatory power with an R² value of 0.64 for marketing performance. These findings indicate that integrating digital marketing with big data analytics capability can enhance marketing effectiveness and strengthen competitive advantage in the logistics industry.